A brief history of pharmacy : humanity's search for wellness - Zebroski, Bob (New York : Routledge, 2016)
'Pharmacy has become an integral part of our lives. Just in the last decade, nearly half of all 300 million Americans take at least one prescription drug daily, accounting for $250 billion per year in sales just in the US alone. And this number doesn't even include the over-the-counter medication, or health aids that are taken. How did this practice become such an integral part of our lives and our health?A Brief History of Pharmacy: Humanity's Search for Wellness aims to answer that question. As this short overview of the practice will show, the search for well-being through the ingestion or application of natural products and more commonly now, artificially derived compounds, is as old as humanity itself. From the Mesopotamians to the corner drug store, Bob Zebroski describes how treatments were sought, highlights some of the main victories of each time period, and shows how we came to be people who rely on drugs to feel better, to live longer, and look younger.'--
'A Brief History of Pharmacy: Humanity's Search for Wellness seeks to explain how pharmacy became an integral part of our lives. From the Mesopotamians to the corner drug store, Bob Zebroski describes how treatments were sought, highlights some of the main victories of each time period, and shows how we came to be people who rely on drugs to feel better, to live longer, and look younger. This accessible survey of pharmaceutical history is essential reading for all students of pharmacy'--
Includes index.
Keywords: Pharmacy -- History